Adult self-regulated learning through linking experience in simulated and real world: A holistic approach - Hetzner, Sonia; et al. (Towards Ubiquitous Learning. EC-TEL 2011., 2011)
This research considers the application of simulated environments for adult training, and adopts the view that effective adaptive solutions for adults should be underpinned by appropriate adult learning theories. Such environments should offer learning experiences tailored to the way adults learn: self-directed, experienced-based, goal- and relevancy oriented. This puts andragogy and self-regulated learning at the heart of the pedagogical underpinnings of the intelligent augmentation of simulated environments for experiential learning. The paper presents a holistic approach for augmented simulated experiential learning. Based on andragogic principles, we draw generic requirements for augmented simulated environments for adult learning. An extended self-regulated learning model that links experiences in simulated and real world is then presented. A holistic framework for augmenting simulators - SRL-A-LRS - is presented and illustrated in the context of the ImREAL EU project. This points at a radically new approach for augmenting simulated systems for adult experiential learnin
Keywords: Self-regulated Learning; Andragogy; TEL Requirements; Simulated Environments for Learning